Kajian Good Governance: Studi di Pemerintah Nagari Simarasok Kecamatan Baso Kabupaten Agam Sumatera Barat Tahun 2011 - Auradian Marta; Raja Amin (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2012)
This research backgrounded by achievement Nagari Simarasok government to role model villagein Indonesia at 2011. This study describes implementation Nagari Simarasok government sosuccesfull to get predicate the best village in national level. It used qualitative method withinformation and date were obtained indepth interview key persons likes wali nagari, kepalajorong, socialite, local government, private sector, and civil society and from the documentsavailable in the village office. The results form research show that Nagari Simarasok governmenthas been practiced the principle of good governance and coordination with private sector andcivil society. Synergi of the governance actor is the key Nagari Simarasok government succesfullat 2011.